Preparation and characterization of digoxin antibody and its application to immunoassays: comparison of performance characteristics between enzyme immunoassay and immunostrip test - Kim, SY; Choi, MJ (ELSEVIER SCIENCE BV, 2000)
After characterizing digoxin immunogens and antibodies, we investigated the assay performances of enzyme immunoassay (ELA), biotin-streptavidin mediated enzyme immunoassay (B-Av EIA), and immunostrip test and compared the effectiveness of these tests fur detecting the presence of digoxin and its analogues. The clinical use of digoxin is very complicated due to its narrow therapeutic range. Thus, the development of a rapid and simple detection device has been needed. In our study, we determined digoxin levels by EIA and B-Av ELA, and compared these tests with the immunotest strip to determine the possibility of personal monitoring at the bedside. Three kinds of digoxin antibodies were produced from various digoxin-BSA immunogens (digoxin/BSA molar ratio of 15:1, 50:1, and 200:1 in their preparation step). The antibodies produced were purified by the immunoaffinity chromatography using digoxin-KLH or digoxin-BSA as the affinity ligand. Antibody #7 and its matching coating ligand of digoxin-KLH were selected by titration and sensitivity studies for use in ELA and B-AV ELA. Colloidal gold-labeled antibody #7 on a glass fiber membrane and digoxin-BSA on a nitrocellulose membrane were selected for the immunostrip preparation. The EIA and B-Av EIA could detect 0.01 ppb digoxin within 2.5 h, but the immunostrip could detect 0.01 ppm within 3 min, which was three orders less sensitive than EIA or B-AV EIA. (C) 2000 Elsevier Science B.V. All rights reserved.